Chemotherapy for Leukemia : Novel Drugs and Treatment - Ueda, Takanori (Springer Singapore : Imprint: Springer, 2017)
This book focuses on the latest progress in chemotherapy for leukemia and related diseases, including still-ongoing but promising studies. The effectiveness of treatment for chronic myeloid leukemia and acute promyelocytic leukemia has been dramatically improved in recent years. This improvement has been made possible with the development of molecular targeted agents such as bcr-abl tyrosine kinase inhibitors and all-trans retinoic acid. The antibody for the unique target of chemokine receptor 4 for adult T-cell leukemia/lymphoma, or FLT3 inhibitors (signaling inhibitors) has been applied to other leukemias. Also, chemotherapeutic agents including antimetabolite analogues such as clofarabine, and azacitidine (an epigenetic regulator) have undergone progressive development. Meanwhile, the novel concept of therapy targeting leukemic stem cells has been developed. The contributors discuss prospective results of basic and preclinical studies and clinical possibilities based on the effects for leukemic stem cells. This work facilitates a comprehensive understanding of modern treatment methodology for leukemia. The volume therefore will greatly benefit not only hematologists but also oncologists, all physicians who specialize in blood cancer, and pharmacologists who are involved in the development of therapeutic agents for leukemia.
Keywords: Medicine.; Hematology.; Oncology.; elektronické knihy; electronic books